Photodegradation of PAHs in passive water samplers. Issue 1 (15th April 2016) - Allan, Ian J.; Christensen, Guttorm; Bæk, Kine; Evenset, Anita
Abstract: Losses of deuterated polycyclic aromatic hydrocarbons (PAHs) used as performance reference compounds (PRCs) in semipermeable membrane devices deployed at fifteen coastal sampling sites near Harstad harbour in Northern Norway were used to investigate photodegradation of these photosensitive compounds. Unusual PRC dissipation profiles, especially for samplers exposed < 5 m below the water surface are indicative of photodegradation. A strong correlation between loss rates for d12 -chrysene and d12 -benzo[e]pyrene with consistently higher losses of the latter was found. The observed photodegradation rates may be sufficiently high to impact PAH masses absorbed by a factor of two. This study demonstrates that photodegradation during exposure of passive water samplers needs to be taken into account, particularly with deployments close to the water surface, when using SPMD canisters, or when sampling in the Arctic. Highlights: Photodegradation of performance reference compounds in passive waters samplers during exposure is observed. Losses of PRCs such as d12 -chrysene and d12 -benzo[e]pyrene may help to identify photodegradation. Photodegradation of chemicals during exposure of passive water samplers can affect the robustness of passive sampling data.